Simulasi Monte Carlo untuk Memprediksi Hasil Ujian Nasional (Studi Kasus di SMKN 2 Pekanbaru) - Yusmaity; Santony, Julius; Yunus, Yuhandri (Jurnal Informasi dan Teknologi, 2019)
Basically grades that do not meet graduation criteria are phenomenon for schools. Which can cause a lack of school quality. One such phenomenon is the National examination Score which is the value of determining graduation for students. Vocatonal High School (SMK) Negeri 2 Pekanbaru is a formal education unit as the organizer of the Teaching Learning Process (TLP), for student afterc ompleting education can go directly to employment or the industrial world and can continue their education. Where the test csores obtained by student are inseparable from the school graduation criteria.To deal whith probalytic situations like this we need a method for analyzing or predict likely in the future. One method that can be used is Monte Carlo Simulation. By using Monte Carlo Simulation to the national exam in this study is expected to holp to find out the acquition of student grades for the future. The csores are taken fom the national exam result obtained from the curriculumsection of the last 3 academic years, namely TP 2016/2017 to TP 2018/2019. This scores is simulationted whith PHP programming as a data implementation system. Simulation result from this studyobtained an accuracy level of 86,68%. By getting a greater degree of accuracy, this method is appropriate to be predict the National Exam Scores for the future.